Hanseníase: conhencendo a doença, prevenindo incapacidades - Garcia, Rosemeire Rodrigues (2014)
Leprosy, also known as Hansen s disease, is an ancient illness which has always been surrounded by prejudice and uninformation. The physical incapacities and organic after-effects of neural damage, determined by the etiologic agent of Hansen s disease, can be diminished by guidelines on self-care provide by physiotherapists. There are a few moments that the patients come into contact with the multidisciplinary team of health, thus hindering these guidelines, so we produce an educational handbook highlighting the importance of self-care to prevent the incapacities caused by leprosy. Therefore, this study aims to identify the level of physical incapacities in patients with leprosy when they first arrive for treatment at the municipal polyclinic of specialties Dr. Edward Maluf , in Sorocaba (SP, Brazil). Using the documentary research method we have analyzed medical records from 2009-2013 from that institution to verify the patients clinical classification and epidemiological aspects in 200 patients seen in that 5 years period. The handbook contains guidelines for self-care and the prevention of incapacities and must be offered in the first consultation by the health team